Montfortian Education Charter (MEC) in the Modern Age: Responding to Global Challenges - Mayod, Bro. Kriangsak (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This article deals with the commitment of the Religious Educators, Montfort Brothers of St. Gabriel, in Thailand and worldwide to cope with changes in the 21st Century. Though their three-hundred-year education system and pedagogy are founded upon the founder’s charism and firm belief in the eternal ’Absolute Truth,’ GOD ALONE, the Montfort Brothers of St. Gabriel acknowledged and responded to constant changes in the world. In response to demands of changes in the 21st Century, 16 years (1992-2008) of revising and updating their educational heritage under the ’Montfortian Education Charter’ (MEC) was successes. Due to their sincere commitment to education mission inherited from their founder and God’s inspiration, the contents of MEC coincide very well with the latest discoveries of educational guidelines for the 21st Century-Partnership for 21st Century Skill and Wagner’s Seven Survival Skills for 21st century students.